Gender Heterogeneity in Self-Reported Hypertension - Eric Bonsang; Eve Caroli; Clémentine Garrouste (Institute of Labor Economics (IZA), 2021)
We investigate the gender gap in hypertension misreporting using the French Constances cohort. We show that false negative reporting of hypertension is more frequent among men than among women, even after conditioning on a series of individual characteristics. As a second step, we investigate the causes of the gender gap in hypertension misreporting. We show that women go to the doctor more often than men do and that they have better knowledge of their family medical history. Once these differences are taken into account, the gender gap in false negative reporting of hypertension is reversed. This suggests that information acquisition and healthcare utilisation are crucial ingredients in fighting undiagnosed male hypertension.
Keywords: I10; I12; J18; 330; gender; objective health; subjective health; hypertension; false negative reporting